Polymeric composite materials of tribotechnical purpose with a high level of physical, mechanical and thermal properties - Kabat, Oleh; Кабат, Олег Станіславович; Sytar, Volodymyr; Ситар, Володимир Іванович; Derkach, Oleksii; Деркач, Олексій Дмитрович; Sukhyy, Kostyantyn; Сухий, Костянтин Михайлович (Національний університет "Львівська політехніка", 2021)
Polymeric composites (PC) of tribological applications with a high level of physical, mechanical and thermal properties based on aromatic polyamide and silica gel have been developed. Regularities have been obtained that describe the effect of the filler content in PC on the friction coefficient, temperature on the friction surface and the intensity of linear wear rate of the studied PC-steel friction pair. It was found that the optimal silica gel content in the polymer matrix is 10 wt %. The morphology of the steel surface of friction after friction interaction with PC based on aromatic polyamide and silica gel was studied. The formation of an antifriction film on the steel surface of friction was discovered, which contributes to a decrease in the friction coefficient, temperature on the friction surface, and the linear wear intensity of the studied PC. The influence of the load and sliding speed on the main tribotechnical characteristics of the PC-steel friction pair has been studied. Mathematical laws were derived that describe the influence of the main external factors (load and sliding speed) on the friction coefficient and intensity of linear wear rate of the studied friction pair. Physical, mechanical and thermal investigations of the developed PC were carried out and it was found that the introduction of 10 wt % silica gel contributes to their 5–10 % increase. Розроблені полімерні композиційні матеріали (ПКМ) триботехнічного призначення з високим рівнем фізико-механічних та теплофізичних властивостей на основі ароматичного поліаміду та силікагелю. Визначені закономірності, які описують вплив вмісту наповнювача у ПКМ на коефіцієнт тертя, температуру на поверхні тертя та інтенсивність лінійного зношування пари тертя ПКМ-сталь. Встановлено, що оптимальним вмістом силікагелю у полімерній матриці є 10 % мас. Проведені дослідження морфології сталевої поверхні тертя після фрикційної взаємодії з ПКМ на основі ароматичного поліаміду і силікагелю. Визначено, що на сталевій поверхні тертя створюється антифрикційна плівка, яка сприяє зменшенню коефіцієнту тертя, температури на поверхні тертя та інтенсивності лінійного зношування ПКМ, що досліджували. Визначено вплив навантаження та швидкості ковзання на основні трибологічні характеристики пари тертя ПКМ-сталь. Отримані математичні залежності, які описують вплив основних зовнішніх чинників (навантаження та швидкість ковзання) на тертя та зношування пари тертя, що досліджували. Проведені фізико-механічні та теплофізичні дослідження розробленого ПКМ та встановлено, що введення у полімерну матрицю 10 % мас. силікагелю сприяє їх 5–10% покращенню.
Полімерні композиційні матеріали триботехнічного призначення з високим рівнем фізико-механічних та теплофізичних властивостей
Keywords: friction unit; вузол тертя; aromatic polyamide; ароматичний поліамід; silica gel; силікагель; polymer composite; полімерний композит; tribological properties; трибологічні властивості; physical and mechanical properties; фізико-механічні властивості